Romanian Knowledge and Attitudes regarding Dietary Fibers - Tarcea, M. (2016)
Presently, the scientists recognize the health benefits of food fibers in the menu and also plant food sources are at high interest both for general population and food companies. The food companies are responsible for a clear nutrition labelling that will assist consumers to make informed and healthy choices and health providers has to inform the population about the benefits of fibers.The aim of our study was to evaluate the Romanian knowledge and attitudes regarding dietary fibers from food products. We made a qualitative survey based on a questionnaire applied in 2015, over a period of 6 months, over 670 Romanian consumers. It was focused on testing the attitudes and knowledge towards ingestion of foods rich in fibers. For all data analysis we used the software SPSS, from IBM Inc. Our results showed that the knowledge about dietary fibers and also the ingestion of food products rich in fibers were low, and most of the subjects didn’t have any interest to read the nutritional information from food labels. The female participants ate more whole grains and fruits than males and pay more attention to food labelling. Romanian people prefer to stay and eat home than at restaurants especially in rural areas, and the knowledge about fibers benefits was significantly related to education and urban location. We underline the needs for more efficient community interventions and proper information about the importance of dietary fibers for our health and also to improve and disseminate nutritional standards and diet recommendation among population.